2004
DOI: 10.2188/jea.14.57
|View full text |Cite
|
Sign up to set email alerts
|

Role of Prehypertension in the Development of Coronary Atherosclerosis in Japan

Abstract: BACKGROUND: Hypertension is an important risk factor of coronary heart disease. A new guidelines for hypertension prevention and management in The Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure in the United States recommended lifestyle modification or medical treatment for subjects with prehypertension. However, whether prehypertension increases the risk of coronary atherosclerosis in the Japanese population is still unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 34 publications
0
34
1
Order By: Relevance
“…Prehypertension is associated with subclinical atherosclerosis, including increased coronary atherosclerosis and increased arterial intima-media thickness. In addition, prehypertension is associated with elevated C-reactive protein, tumour necrosis factor α, homocysteine, oxidized low-density lipoprotein cholesterol and other inflammatory markers [9,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Prehypertension is associated with subclinical atherosclerosis, including increased coronary atherosclerosis and increased arterial intima-media thickness. In addition, prehypertension is associated with elevated C-reactive protein, tumour necrosis factor α, homocysteine, oxidized low-density lipoprotein cholesterol and other inflammatory markers [9,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of the increased cardiovascular disease risk related to the coexistence of prehypertension, glucose intolerance, and diabetes suggest that pharmacological intervention for blood pressure control in these groups may be warranted to prevent cardiovascular disease morbidity and mortality, as suggested by others. 19 A clinical trial is needed to confirm this. Increased age, higher body mass index, LDL cholesterol, and triglyceride levels, lower HDL levels, current smoking, ex-alcohol use, and male gender were all related to significantly increased cardiovascular disease risk.…”
Section: Discussionmentioning
confidence: 99%
“…12 In another longitudinal study, Winegarden 11 showed that, relative to normotensive subjects, the risk of hypertension was substantially higher among subjects with "high normal" BP (130 to 139/85 to 89 mm Hg). However, whereas several reports have documented an increased risk of CVD among prehypertensive subjects, 5,6,8,12,13 others suggest that prehypertension increases the risk of CVD only modestly or that this risk increases only when prehypertension is associated with additional risk factors. 4,7 Data on prehypertension in young adults are lacking, and little is known on the risk factors for prehypertension and their association with other CVD risk factors.…”
mentioning
confidence: 98%